Rekonsiliasi Islam Dan Demokrasi: Narasi Politik Benazir Bhutto - Lukman Santoso (AL-TAHRIR, 2016)
Abstract: Pakistan, since independence, there are differences of opinion among the Muslims of Pakistan consisting of secularists, moderate Islamists about how should the implementation of the Islamic politics in Pakistan, giving rise to a prolonged political crisis when today. Pakistan's political turmoil unending birth Pakistani women politicians and thinkers, namely Benazir Bhutto. This paper will focus on the study of Benazir Bhutto thinking about the relationship between Islam and democration in Pakistan. Based on the results of the study, there are some findings: First, Benazir with thoughts that category substantivistik and relatively conflict with Muslim-majority Pakistan (traditionalists and fundamentalists), the ideas in tune with existence, articulation, and a manifestation of Islamic values are intrinsic in the climate modern democrations. Second, the idea of Benazir is a counter discourse to the idea that idealized which Islam should be the political system. Benazir thinking is in line with the paradigm who saw that Islam does not lay down a standard pattern of the theory of the political system must be organized by the people, except for the values and ethical principles.الملخص :كانت في باكستان – منذ حرّيتها – خلافات الآراء عند المسلمين بين العلمانيين والمتوسطين والإسلاميين عن كيفية تطبيق السياسة الإسلامية في باكستان حتى أدّت إلى النزاع السياسيّ الطويل إلى الآن. وظهرت في هذه الفترة النزاعية مفكّرة وسياسيّة بينزر بوطو. حاولت هذه المقالة التركيز في دراسة أفكارها عن التصالح الإسلامي والديموقراطية في باكستان. حصلت هذه الدراسة على النتائج : أولا، كانت بينزر بوطو بما لها من أفكار تميل إلى الأصالة وأفكارها متعارضة بأغلبية المسلمين التقاليديين والأصوليين، وكانت أفكارها موافقة بمكانة القيم الإسلامية الأصيلة وتمثيلها وتطبيقها في ضوء الديموقراطية الحديثة. ثانيا إن هذه الأفكار كردّ تجاه الفكرة المؤيّدة ليكون الإسلام أساسا للدولة. كانت هذه الأفكار تواكب بفكرة أن الإسلام لا يضع نظرية معيّنة لبناء الدولة يعتنقها المسلمون إلا الأسس العامة فقط  والقيم فيها.Abstrak: Pakistan, sejak kemerdekaannya, terdapat perbedaan pendapat dikalangan kaum muslim Pakistan yang terdiri dari kelompok sekular, moderat dan Islamis tentang bagaimana implementasi Islam politik di Pakistan, sehingga menimbulkan kemelut kekuasaan yang berkepanjangan hingga kini. Ditengah kemelut politik Pakistan yang tidak berkesudahan tersebut lahirlah politisi dan pemikir perempuan Pakistan, yakni Benazir Bhutto. Tulisan ini akan memfokuskan kajian pada pemikiran Benazir Bhutto tentang rekonsiliasi Islam dan demokrasi di Pakistan. Berdasarkan hasil kajian, terdapat beberapa temuan, yaitu: Pertama, Benazir dengan pemikirannya yang termasuk kategori substantivistik dan tergolong bertentangan dengan mayoritas muslim Pakistan (tradisionalis dan fundamentalis) ini, gagasannya selaras dengan eksistensi, artikulasi, dan manifestasi nilai-nilai Islam yang instrinsik dalam iklim demokrasi modern. Kedua, gagasan Benazir merupakan counter wacana terhadap pemikiran yang mengidealkan bahwa Islam harus menjadi dasar negara. Pemikiran Benazir ini selaras dengan paradigma yang melihat bahwa Islam tidak meletakkan suatu pola baku tentang teori sistem politik yang harus diselenggarakan oleh umatnya, kecuali nilai-nilai dan prinsip-prinsip etisnya.